STUDENTS’PERCEPTION USING INSTAGRAM REELS TOWARD SPEAKING ABILITY IMPROVEMENT: ENGLISH DEPARTEMENT STUDENTS’ VOICE - Aprian, Wenny; Oktavia, Diana; Trisnawati, Winda (Universitas Muhammadiyah Muara Bungo, 2023)
This study aims to determine students' perceptions about using Instagram reels to improve speaking ability. This research used descriptive qualitative research instruments by conducting interviews with 10 students who have used Instagram reels as a medium to improve their speaking ability in the English Department at Muhammadiyah University of Muara Bungo. The researcher found, referring to the results of student interviews, that most students gave a positive perception of using the Instagram reel application. Several obstacles cause the learning process to be ineffective, ranging from disturbances caused by other Instagram users that cause students not to focus on the learning process and can cause concentration disturbances to fraudulent fraud that occurs on Instagram, which causes students confusion when trying to find an account for learn to improve speaking ability.